Acoustic wave velocity in Ag/Fe nanolayers - Aleksiejuk, Mikołaj; Rejmund, Feliks (Archives of Acoustics, 2007)
The paper presents the results of acoustic wave velocity investigation in metallic Ag/Fe nanolayers deposited on GaAs substrate. Measurements of velocity were performed using femtosecond technique. Ag/Fe samples were characterized by different thickness of bilayers. On the basis of experimental results of velocities, effective elastic constants c_11 were evaluated. In the range of bilayers thickness above 80 Å the c_11 values are in accordance with those calculated from the elastic constants of bulk materials (Rytov model). For lower values of bilayer thickness elastic constants exhibit large decrease. Grimsditch’s model was applied to interpret changes of elastic constants dependence for low bilayer thickness. This model contains an additional interlayer treated as the parameter. Comparison the values of theoretical elastic constants obtained by applying of Grimsditch model with those calculated from experiment shows qualitative accordance in the range of small bilayer thickness.